Case-control study of risk factors for disease in the neck and shoulder area. Issue 4 (April 1994) - Ekberg, K; Björkqvist, B; Malm, P; Bjerre-Kiely, B; Karlsson, M; Axelson, O
Abstract : A case-control study was performed to elucidate the strength of the relation between musculoskeletal disorders in the neck and shoulders and physical, organisational, and psychosocial aspects of the work environment. Cases were identified as those persons who consulted a physician in a community in southern Sweden for new musculoskeletal disorders in the neck and shoulders during a study period from August 1988 to the end of October 1989. One hundred and nine cases were collected and clinically examined. The cases also answered the Nordic questionnaire on symptoms as well as a questionnaire on work conditions and background factors. Controls were drawn as a random sample of the working population in the community where the cases appeared. A total of 637 controls answered the same questionnaires as the cases. Odds ratios (ORs) were calculated by logistic regression. The odds ratios were 11.4 for women, 4.9 for immigrant background, and 3.7 for current smoking. To exercise rarely, compared with often, appeared as a preventive factor with an OR of 0.3. The ORs for various determinants of physical work load were 7.5 for repetitive movements demanding precision, 13.6 for light lifting, 3.6 for uncomfortable sitting positions, 4.8 for work with lifted arms, and 3.5 for a rushed work pace. Regarding work organisational determinants, the ORs were 16.5 for ambiguity of work role (uncertainty whether the person could manage the work) 2.6 for low quality work, and 3.8 for high demands on attention. Several of the determinants showed a significant dose-response relation with disease. It seems that work organisation and psychosocial work conditions are as important determinants for disease in the neck and shoulders as are the physical work conditions.